Surveiller et guérir le corps optimal: Big Data et performance sportive - Dalgalarrondo, S. (L'Homme & la Société, 2018)
Professional sport and its intensive medicalization of performance appear as one of the privileged places for shaping representations of the body. The production of a sport performance requires to reach the physiological and psychological limits of the athlete. Professional sport is therefore a laboratory of extremes where knowledge, techniques, values and norms are articulated in order to approach the maximum productivity of the body. In this perspective, we propose to analyse the promise of Data Tracking technologies. This article aims to identify the political issues related to the deployment of these monitoring devices.